2007
DOI: 10.1038/oby.2007.214
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Psychosocial Factors on Quality of Life in Overweight Youth

Abstract: Objective: The psychosocial functioning of overweight youth is a growing concern. Research has shown that overweight children report lower quality of life (QOL) than their non-overweight peers. This study sought to extend the literature by examining the association between peer victimization, child depressive symptoms, parent distress, and health-related QOL in overweight youth. Mediator models are used to assess the effect of child depressive symptoms on the relationship between psychosocial variables and QOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
109
5
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 56 publications
16
109
5
7
Order By: Relevance
“…However, Bland-Altman plots showed a systematic bias Health-related quality of life in obese children and adolescents MD Tsiros et al between parent-and pediatric-reported scores ( Figure 4, r ¼ À0.58, P ¼ 0.015, n ¼ 12), with parents rating HRQOL lower than youths when scores were low (o75-85), and higher when scores were high (485). Similarly, many pediatric obesity studies find parent proxy reports of HRQOL to be lower than pediatric reports, 6,11,12,24,26,[28][29][30]35 with the exception of one population-based study, 6 which found less agreement between parent proxy and child-reported HRQOL in a 12-year-old age group compared with younger children. The pooled analyses conducted in this review showed that pediatric self-ratings became progressively more positive than parent ratings with increasing age (Figure 4, r ¼ À0.54, P ¼ 0.03, n ¼ 12).…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…However, Bland-Altman plots showed a systematic bias Health-related quality of life in obese children and adolescents MD Tsiros et al between parent-and pediatric-reported scores ( Figure 4, r ¼ À0.58, P ¼ 0.015, n ¼ 12), with parents rating HRQOL lower than youths when scores were low (o75-85), and higher when scores were high (485). Similarly, many pediatric obesity studies find parent proxy reports of HRQOL to be lower than pediatric reports, 6,11,12,24,26,[28][29][30]35 with the exception of one population-based study, 6 which found less agreement between parent proxy and child-reported HRQOL in a 12-year-old age group compared with younger children. The pooled analyses conducted in this review showed that pediatric self-ratings became progressively more positive than parent ratings with increasing age (Figure 4, r ¼ À0.54, P ¼ 0.03, n ¼ 12).…”
Section: Resultsmentioning
confidence: 84%
“…In contrast, three smaller cross-sectional studies from the United States of America did not find a significant inverse relationship between BMI (as a continuous predictor) and overall HRQOL. 13,28,29 Physical functioning. When examining subsets of HRQOL, 12 studies report significantly lower physical functioning in obese compared with lean children 6,11,12,15,17,23,24,27,28,[30][31][32] ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations